Iliac Artery Injury With Foreign Body: A Unique Case Of Child Abuse - Baransel Isir, Aysun; Tokdemir, Mehmet; Parmaksiz, Ergun; Rahman, Ali; Kazez, Ahmet (Pera Yayincilik Hizmetleri, 2008)
The aim of this study is to discuss physical abuse part of a case by presenting a rarely seen injtmy which is vaginal bleeding 8-month-old girl with an unknown story. At further analyze and operation, she was operated on for a 4.2 cm long foreign body which caused both perforation in the uterus and injury to the right iliac artery. Four days after the operation, she had sudden toss of vision, intracranial bleeding and generalized convulsion. Three months later, it was encountered that she had an amputated distal phalanx in the 5th finger on the right hand. Social and medico-legal management of physical abuse is suboptimal in Turkey. In this way, an emphasis is made on the necessity of subject keeping in mind when injuries without any sufficient reliable data are encountered as the physical abuse.
Keywords: Child abuse; foreign body; iliac artery injury; phalanx amputation